PENGARUH TINGKAT KEPADATAN JENTIK AEDES AEGYPTI TERHADAP KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI DESA PANDANSARI KECAMATAN PONCOKUSUMO KABUPATEN MALANG - Vira Tika Yuniar; Rudy Joegijantoro; Septia Dwi Cahyani (Jurnal Higiene Sanitasi, 2022)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus which is transmitted from person to person through the bite of a female Aedes Aegypti sp mosquito that contains the dengue virus. Dengue virus is a member of the flavivirus genus which has 4 serotypes, namely Den-1, up to Den-4. Aedes aegypti and Aedes albopictus are mosquitoes which transmit dengue disease. The purpose of this research is to analyze the influence of the density level of Aedes Aegypti mosquito larva on the Incidence of Dengue Fever (DHF) at Pandansari Village, Poncokusumo District, Malang Regency. This research method was cross-sectional research. The population of this research are all houses in Pandansari Village, ammounted as much as 1520 houses. The sample were taken by simple random sampling and obtained a sample of 316 houses consisting of 3 kampoongs namely Krajan (192 Houses), Wonosari (69 Houses), and Sukosari ( 55 Houses). Based on the research results it is found that the index house (HI) in Pandansari Village is (87.75%), container index (CI) (54.79%), Bretue index (BI) (101.2%), and ABJ (14.2%). the results of statistical test using logistic regression test showed that there is an effect but not significant between the level of larva density and the incidence of DHF. The density of Aedes Aegypti larvae has an effect of 17.6% and 82.4% which influenced by other factors. So, it is suggesled for the people who live at Pandansari, Poncokusumo District, to maintain the cleanliness of the water tub to be drained at least once a week, and cover the water reservoir, so that the mosquitoes can not lay eggs there.